Acoustic Droplet Ejection Applications for High-Throughput Screening of Infectious Agents. (February 2016) - Rasmussen, Lynn; White, E. Lucile; Bostwick, James R.
When acoustic droplet ejection technology was first introduced for high-throughput applications, it was used primarily for dispensing compounds dissolved in DMSO. The high precision and accuracy achieved for low-volume transfers in this application were noted by those working outside of the compound management area, and interest was generated in expanding the scope of the technology to include other liquid types. Later-generation instruments included calibrations for several aqueous buffers that were applicable to the life sciences. The High Throughput Screening Center at Southern Research has made use of this range of liquid calibrations for the Infectious Disease Program. The original calibration for DMSO has allowed the preparation of assay-ready plates that can be sent to remote locations. This process was used as part of the collaboration between Southern Research and Galveston National Laboratory, University of Texas Medical Branch, to develop high-throughput screening for biological safety level 4 containment and to provide compounds for two pilot screens that were run there with BSL-4-level pathogens. The aqueous calibrations have been instrumental in miniaturizing assays used for infectious disease, such as qPCR, tissue culture infectious dose 50, and bacterial motility, to make them compatible with HTS operations.